MIGRATION POLICY AND THE CROSS-BORDER SECURITY - Wawrzusiszyn, Andrzej (Torun International Studies, 2017)
Poland interests and her policy are strongly determined by her geopolitical conditions. More than 40 years of people democracy under USSR domination brings in whole region civilization and economic backwardness. After 1989 Poland attempts to “catch up” the Old Europe. Initiative of Three Seas is one of such attempt. Increasing relations with central and southern Europe especially in case of diversification of raw materials – like gas – can bring to region an independence from Russian supplies. Three Seas goes back to conception of Intermarium, and redefine her on amended conditions of modern world. In this article the Authors will present short history of conception Intermarium, main assumptions of polish foreign policy and will try to answer the question is this conception is still present in polish foreign policy, even if in changed form of Three Seas.